UJI EFEKTIVITAS ANTIFUNGI EKSTRAK ETANOL BATANG BROTOWALI (Tinospora crispa) TERHADAP PERTUMBUHAN Trichophyton rubrum SECARA IN VITRO - Nurul Nadifa Erza (2020)
Trichophyton rubrum is infectious dermatophyte fungus which is the most common cause of dermatophytosis. Fungal resistance and the side effects of therapy are problems of antifungal agents. Phytochemical test of brotowali stem extract (Tinospora crispa) consist of flavonoids, phenols and triterpenoids which have antifungal effects. The purpose of this study was to examine the effectiveness of brotowali stem extract (Tinospora crispa) as antifungal agent towards the growth of Trichophyton rubrum in vitro by agar well difussion method. The experimental method was used in this research with post test only control group design using brotowali stem extract concentration of 10%, 12,5%, 25%, 30%, 40%, 50%, 60%, 75%, 100%, ketoconazole as positive control and aquades as negative control. Brotowali stem extract concentration of 10%, 12,5%, 25%, 30%, 40%, 50%, 60%, 75% and 100% produced an average diameter of 2,167 mm, 6,367 mm, 7,0 mm, 10,67 mm, 11,9 mm, 13,07 mm, 15,8 mm, 17,96 mm and 17,13 mm respectively, followed by Ketoconazole 35,7 mm. There are significant differences between each treatment group, p = 0,001 (p<0,05). Brotowali stem extract (Tinospora crispa) has weak antifungal effectiveness at concentration 10%, 12,5%, 25%, intermediate antifungal effectiveness at concentration 30% and strong antifungal effectiveness at concentration 40%, 50%, 60%, 75% and 100% in inhibiting the growth of Trichophyton rubrum in vitro by well difussion method.